Patterns of contemporary ijtihad in Malaysia: Analysis on fatwas of Malaysian National Fatwa Council - Man, S. (2014)
The exercise of ijtihad (independent reasoning by qualified jurist) has been a siginificant process in the development of Islamic Law as witnessed throughout the history of Muslim society. Ijtihad has always been an important tool and source for Muslims to find Islamic rulings on various current and newcoming issues which they found no direct answers both in the Quran and the Prophet Muhammad’s traditions. As a largest community in Malaysia, Muslim society which form 60% of 30 million of total population experiences a lot of new issues in their current life, from issues of personal religious duties to various mundane issues such as economics, ethnic relations, medicines etc. The urgent need of religious answers for these issues has engendered a rapid growth of ijtihad in its various form: fatwas (edicts), academic researches and legislation. This paper focuses on fatwas issued by Malaysian National Fatwa Council as it is regarded as highest and respectable religious institution in Malaysia. This institution has issued more than three hundred fatwas since its establishment in 1970. In completing this paper the reasearcher uses the datas acquired through funded research grant by University Malaya (RG421-12HNE) which is undertaken from 2012 until 2014.